DEVELOPMENT OF THE KOREAN POETIC DRAMA AND THE SIGNIFICANCE OF THE POETIC DRAMA MOVEMENT - LEE, Hyeon-Jeong (International Journal of Korean Humanities and Social Sciences, 2021)
This paper deals with the definition and characteristics of poetic drama, and attempts to clarify the significance of poetic drama works during the time when the poetic drama movement took place. Unlike drama-poetry or plays, poetic drama is an independent art genre. It presents artistic vision through the conflict of poetics and dramas. The unity of poetic and dramatic things, which is facilitated through music, internal necessity, stage image, sound effect, and visual auditory indication, poetic drama is a part of complex art. The entire work functions as a poem and must be realized on the stage. For Choi Il-soo, in order to develop the characteristics of these poetry plays, the innatrhythm of the free verse should be embodied within these plays. He accepted Eliot’s theory and tried to establish the position that Western poetic drama works and theories are unique to Korea. This deepening perception of theory led to a poetic drama movement with the creators. In this paper, we classify its characteristics by focusing on approximately 18 poetic drama works. From 1920 to 1999, 18 representative works were classified, focusing on the completeness of the works and the remarkable artists. The characteristics of works can largely be divided into historical, narrative, reality, and philosophy. The meaning of this classification can serve as an opportunity for poetic dramas to advance into more diverse topics or forms. The poetic drama movement was dominated by critics and poets with the aim of pursuing independent Korean art works, and although it failed in performance and popularization, it was an achievement of the times to give a glimpse into the possibility of poetic drama. Poetic drama can act as a new element in the genre of poetry and drama that are losing original literary character, and there is a need to revive in Korean literature.